Price Changes and Trading Volume Relationship: Some Preliminary Evidence from the Kuala Lumpur Stock Exchange - Mohamad, Shamsher; Md Nassir, Annuar (Universiti Putra Malaysia Press, 1995)
This study provides evidence regarding the relationship between price changes and volume of trading of firms listed on the KLSE. Absolute price changes were found to have a strong relationship with trading volume compared to price changes. Transaction volume associated with a price upturn was, on the average, larger than the transaction volume associated with a price downturn which probably explained the positive correlation between price changes and trading volume. Causality tests indicated that price changes cause volume changes but not vice versa. The interaction test showed that large transaction volume coupled with an increasing trend in price will further gather momentum and result in a further increase in price. This fll1ding, however, does not suggest that the KLSE is weak-form inefficient which provides an opportunity to investors to devise strategies as there is evidence that the KLSE is weak-form efficient and pockets of inefficiencies observed are not economically viable. The findings defy the basic tenet of technical analysis that past price volume data can be consistently used to design profitable investment strategies.